Analisis Sektor Unggulan di Kabupaten Bengkulu Selatan Menurut Perspektif Islam - Velyanita; Asnaini; Rahmat Putra Ahmad Hasibuan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the leading sectors in South Bengkulu district based on Islamic perspectives. This study uses the Location Quotient (LQ) method to identify superior sectors, Shift Share Analysis (SSA) to see sectoral growth, and descriptive analysis to relate the findings to Islamic economic principles. The data used is secondary data in the form of Gross Regional Domestic Product (GDP) of South Bengkulu Regency and Bengkulu Province in a certain period. The results of the study show that the Inventory Change sector. This sector can become a leading sector in South Bengkulu because it meets the applicable provisions in determining the superior sector, namely having an average value of LQ > 1 and positive values in the Mij component and the Cij component in the Shift Share analysis. This research recommends the development of leading sectors with an Islamic approach, such as strengthening the Islamic financial system, increasing the capacity of farmers and fishermen, as well as resource management based on Islamic values. The results of this research are expected to be the basis for sustainable and sharia-based regional economic development planning.